Implementasi Penilaian Autentik dalam Evaluasi Pembelajaran Bahasa Arab pada Kelas XI Madrasah Aliyah Nurul Iman - Syamsul Huda; Yeni Nuriah Fitri (Universitas Serambi Mekkah, 2026)
This study aimed to analyze the implementation of authentic assessment in Arabic language learning evaluation, describe its assessment management, and examine teachers' optimization strategies in eleventh-grade classes at Madrasah Aliyah Nurul Iman. A qualitative approach with a case study design was employed. Seven informants participated in the study, consisting of the principal, vice principal for curriculum, an Arabic language teacher, and four students. Data were collected through observations, semi-structured interviews, and document analysis and analyzed using the interactive model of Miles and Huberman. The findings indicate that authentic assessment has been comprehensively implemented through integrated affective, cognitive, and psychomotor assessment. Assessment management is systematically carried out through planning, instrument development, assessment implementation, documentation of learning outcomes, and feedback provision. Its optimization is supported by teacher reflection, assessment innovation, the use of assessment results, technology integration, and continuous refinement of assessment instruments. These findings affirm that authentic assessment functions as an integrated evaluation system that supports more comprehensive, objective, adaptive, and sustainable Arabic language learning